Virtual Reality Bridging the Gap Between Work Experience Required and University Qualifications in South Africa (Proceedings of the International Conference on Education, 2020)
Pervasive technologies such as Virtual Reality are making our working life and education to become more digital, complex and interconnected. The job landscape has already been disrupted by the Fourth Industrial Revolution (FIR). The way we work and learn is set to be transformed as the jobs people have and required skills necessary for success are some of the areas most impacted by technological advances such as the FIR and this is particularly concerning for the South African context. New ways of education are required in order to allow future employees to flexibly react to the future world of work and meet the demands of such a digitised working environment. The aim of the research was to identify the present forces, trends and drivers of change that impact the future of education and the future of work. The Six Pillars of Futures Studies approach to research by Inayatullah was applied throughout the study to address the research question: What are the possible futures for tertiary education and jobs in South Africa; and how can the tertiary education providers and the corporate world, through the use of Virtual Reality, explore the potential and extent to which Virtual Reality can be used in bridging a gap between work experience required and university qualifications in South Africa towards the future? The study developed four different future scenarios and the most favourable scenario was used to formulate the recommended vision, "Future Vision of Education and Work in South Africa towards 2030" which envisages an education system that broadens access to opportunities and provides the skills and competences that people need to thrive in a new sustainable economy.
Keywords: Virtual Reality, Future of Education, Future workforce, Skills Transformation, Fourth Industrial Revolution, Futures Studies